Can Evidence Impact Attitudes? Public Reactions to Evidence of Gender Bias in STEM Fields. (June 2015) - Moss-Racusin, Corinne A.; Molenda, Aneta K.; Cramer, Charlotte R.
Our research capitalized on a naturalistic data collection opportunity to investigate responses to experimental evidence of gender bias within science, technology, engineering, and mathematics (STEM). We analyzed 831 written comments made by members of the public in response to three prominent articles reporting on experimental evidence of science faculty members' gender biases. Utilizing a mixed-method approach (i.e., thematic and quantitative analysis), we identified the nature and frequency of positive and negative responses, and we investigated possible gender and professional differences in what commenters wrote. Although acknowledgment of gender bias was the most prevalent category, a wide range of positive (e.g., calls for social change) and negative (e.g., justifications of gender bias) reactions emerged. Among the subsample of 423 comments for which it was possible to code commenters' gender, gender differences arose for the majority of categories, such that men were more likely than women to post negative responses and women were more likely than men to post positive responses. Results were unaffected by commenters' own STEM field affiliation. We discuss implications for the role of clearly demonstrated bias in prejudice recognition and reduction as well as the development of STEM diversity interventions.